La obra de Ricardo Palma anté su época: ¿crónica y/o testimonio? - Sagermann Bustinza, Leonor (My University, 2010)
Ricardo Palma, one of the most distinguished Peruvian writers, is known worldwide thanks to his Peruvian Traditions, a series to which he dedicated a considerable part of his life. The objective of this paper is to present other aspects of his literary and journalistic activity and to assess the value of his writings from the perspective of contemporary chronicle and testimony.
Keywords: chronicle; history; Peru